EFFECT OF DIFFERENT SOLVENTS ON ANTIOXIDANT ACTIVITY OF LEAF EXTRACTS OF CALOTROPIS PROCERA AND AZADIRACHTA INDICA - Banerjee, Sharmistha; Kaushik, Shuchi; Tomar, Rajesh Singh (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study was performed to identify the phytochemicals and comparatively evaluate the antioxidant activity of Calotropis procera and Azadirachta indica by detection of total phenolics, hydrogen peroxide radical scavenging activity, and estimation of condensed tannins in different solvent systems and at different temperatures. Methods: Leaves of C. procera and A. indica were extracted in water, methanol by soaking dried leaf powder at room temperature and also by boiling the leaf powder in water for 30 minutes. Phytochemical tests were performed in all of the extracts. The antioxidant activity was determined by hydrogen peroxide radical scavenging activity. Quantitative estimation of total phenolics and hydrolysable tannins was also performed. Results: The total phenolics in both leaf extracts was obtained maximum in boiled extract (40.7±1.20 mg gallic acid equivalent [GAE]/g dry extract in C. procera and 33.66±1.45 mg GAE/g dry extract in A. indica). The amount of hydrolysable tannins in both leaf extracts was found to be highest in methanol (150±1.88 mg catechin equivalent/g dry extract in C. procera and 144.8±2.63 mg catechin equivalent/g dry extract in A. indica). Conclusion: The study showed promising results indicating that these plants are a good source of antioxidants. The majority of phytochemicals were extracted in distilled water and methanol acts as a good solvent for extraction of tannins, whereas an increase in temperature leads to poor extraction of tannins. Keywords: Antioxidant, Phytochemicals, Phenolics, Radical, Tannins.